(untitled) (Biological Sciences - PJSIR, 2000)
Mineral levelsof trace(Cd, Zn, Ni, Fe,CuandCo) and macro(Ca, Mg, Na, K and P) weredetermined infour prawns: Macrobrachium vollenhovenii, Pa/aemon speciesA,Penaeus notialis andPenaeus kerathurus intheLagoslagoonwater in Epe area of LagosState,Nigeria.The levelsof Cd,Zn, Ni, Fe, Cu, Na, and P werehigher in prawn samplesthan in water while Mg was more concentrated in water but Co was not detected in water. There was evidence of mineral bioconcentration in all the samples. Individual prawn mineral concentration followed the following patterns: M vollenhovenii >P notialis > P species A> P kerathurus (fortraceminerals)and P kerathurus > P notialis > P species A >M vollenhovenii formacromineralssuggestingthatmineralconcentrationmaybea factorof sizeand species.